2020
DOI: 10.1007/s10649-020-09984-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative judgement, proof summaries and proof comprehension

Abstract: Proof is central to mathematics and has drawn substantial attention from the mathematics education community. Yet, valid and reliable measures of proof comprehension remain rare. In this article, we present a study investigating proof comprehension via students’ summaries of a given proof. These summaries were evaluated by expert judges making pairwise comparisons, which were used to generate a score for each summary. This approach, known as comparative judgement, has been demonstrated to generate reliable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…1. These proof summaries were a subset of an existing dataset, presented in Davies et al (2020), and were responses to the prompt shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1. These proof summaries were a subset of an existing dataset, presented in Davies et al (2020), and were responses to the prompt shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
“…RQ3: How can these features be used to account for the consistency amongst judging mathematicians identified in Davies et al (2020)?…”
Section: Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted above, Mejía-Ramos et al (2021) used CJ to determine mathematicians' views of the explanatory value of a collection of proofs. Other recent work has used CJ to investigate students' comprehension of proofs by judging the quality of their written summaries of proofs (Davies et al, 2020), and to investigate mathematicians' and undergraduate students written conceptions of mathematical proof (Davies et al, 2021).…”
Section: Comparative Judgementmentioning
confidence: 99%